Dielectric barrier discharge plasma grafting carboxylate groups on Pt/Al2O3 catalysts for highly efficient hydrogen release from perhydro-dibenzyltoluene. Issue 5 (25th January 2022) - Shi, Libin; Zhou, Yiming; Tan, Xiao; Qi, Suitao; Smith, Kevin J.; Yi, Chunhai; Yang, Bolun; Liu, Shida
Abstract : The carboxylate groups on Pt/Al2 O3 catalysts increase the proportion of Pt (1 1 1) and Pt (1 0 0) planes that facilitate H18-DBT dehydrogenation. Abstract : The key issues for the use of dibenzyltoluene (DBT) as a liquid organic hydrogen carrier (LOHC) are the high dehydrogenation temperature and the sluggish hydrogen releasing rate. Therefore, highly active catalysts are urgently needed for the dehydrogenation process. Towards an increased perhydro-dibenzyltoluene (H18-DBT) dehydrogenation rate, dielectric barrier discharge (DBD) plasma pretreatment was adopted to modify Pt/Al2 O3 catalysts. As revealed by various characterization methods, methyl, methylene and carboxylate groups were grafted on Al2 O3 and S 2− and SO4 2− groups were grafted on Pt/Al2 O3 after DBD plasma treatment. The Pt dispersion, the different proportions of different crystal planes, the low coordinated Pt sites and hydrogen spillover on the catalyst surface were modified. The catalyst with carboxylate groups showed the highest dehydrogenation productivity and produced the least amount of by-products. These improvements in the catalysts' performance were confirmed and are attributed to the higher proportion of exposed Pt (1 1 1) and Pt (1 0 0) planes, fewer low coordinated Pt sites and more hydrogen spillover.